1983
DOI: 10.1086/208954
|View full text |Cite
|
Sign up to set email alerts
|

Central and Peripheral Routes to Advertising Effectiveness: The Moderating Role of Involvement

Abstract: Undergraduates expressed their attitudes about a product after being exposed to a magazme ad under conditions of either high or low product involvement. The ad contained either strong or weak arguments for the product and featured either prominent sports celebrities or average citizens as endorsers. The manipulation of argument quality had a greater impact on attitudes under high than low involvement, but the manipulation of product endorser had a greater impact under low than high involvement. These results a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

102
2,402
11
124

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,470 publications
(2,758 citation statements)
references
References 45 publications
102
2,402
11
124
Order By: Relevance
“…Consumer research has indeed shown that celebrity endorsement may enhance the recall of advertising messages, increase the recognition of brand names and make advertisements more believable (Friedman and Friedman, 1979;Kamins et al, 1989;Petty et al, 1983). However, whether celebrities are also able to improve purchase intentions is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…Consumer research has indeed shown that celebrity endorsement may enhance the recall of advertising messages, increase the recognition of brand names and make advertisements more believable (Friedman and Friedman, 1979;Kamins et al, 1989;Petty et al, 1983). However, whether celebrities are also able to improve purchase intentions is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…Level of involvement is determined with respect to how much active engagement is needed for productfocused judgment and decision-making (Petty, Cacioppo, and Schumann 1983;Zaichkowsky 1985). Consumers develop diversified involvement levels through product categories (Manzur et al, 2012).…”
Section: Product Involvementmentioning
confidence: 99%
“…Favourable brand responses are likely when consumers perceive a celebrity -brand pairing as relevant (Keller, 2013), use of celebrity in an advertisement amplify brand awareness, draw the attention of celebrity's fans, augment trial and purchase confidence (Chan et al, 2013), advertisers too strongly believe that celebrity involvement enhance effectiveness of advertising, enhance brand recall, recognition, purchase intentions and follow-through (Spry et al, 2011). Celebrity's physical attractiveness matters for purchase intention especially when the product is used to enhances the physical appearance and physically attractive celebrities are more effective, eventually result in positive consumer preference (Biswas et al, 2006;Erdogan, 1999;Joseph, 1982;Kamins, 1990;Petroshius and Crocker, 1989;Petty et al, 1983;Tantiseneepong et al, 2012;Till and Busler, 2000). Further the likeability of celebrity is also crucial including their physical attractiveness, expertise and trustworthiness (Biswas et al, 2006;Kamins, 1990;Tantiseneepong et al, 2012).…”
Section: Celebrity Endorsementmentioning
confidence: 99%